Frequency of neonatal abstinence syndrome (NAS) and type of the narcotic substance in neonates born from drug addicted mothers - Fatemeh Nayeri; Mamak shariat; Majeed Firozi; Majeed Kalani; Bita Ebrahim (Mashhad University of Medical Sciences, 2015)
Abstract Background and objective: NAS is a combination of signs and symptoms that due to physical and mental dependency, develops in neonates born from drug addicted mothers. The onset of NAS varies in accordance with the type, amount, frequency and duration of substance used. Because of diverse and unclear pattern of substance abuse in Iranian addicted pregnant mothers in comparison with western countries, this multi-center study has been designed to evaluate NAS in neonates born from drug addicted mothers. Material and method: A cross sectional study was carried out on newborns of narcotic addicted mothers during the first six months of 2008. The newborn's status and clinical signs were checked by physical examination and scored by the Finnegan scoring system. Results: In this study 100 neonates born from narcotic addicted mothers were examined; the most used narcotic was crack (36%). 60% of neonates showed signs of NAS. The most prevalent signs of NAS were increased muscle tonicity (60%/7), irritability (59%/6) and increased moro reflex (51%/8). Neonates born from crack abusers, in comparison with other drugs, were significantly at risk of NAS (100% vs.87%, p